The aryl hydrocarbon receptor: A predominant mediator for the toxicity of emerging dioxin-like compounds - Zhang, Wanglong; Xie, Heidi Qunhui; Li, Yunping; Zhou, Mingxi; Zhou, Zhiguang; Wang, Renjun; Hahn, Mark E; Zhao, Bin (Journal of hazardous materials, 2022)
The aryl hydrocarbon receptor (AHR) is a member of the basic helix-loop-helix/Per-ARNT-Sim (bHLH-PAS) family of transcription factors and has broad biological functions. Early after the identification of the AHR, most studies focused on its roles in regulating the expression of drug-metabolizing enzymes and mediating the toxicity of dioxins and dioxin-like compounds (DLCs). Currently, more diverse functions of AHR have been identified, indicating that AHR is not just a dioxin receptor. Dioxins and DLCs occur ubiquitously and have diverse health/ecological risks. Additional research is required to identify both shared and compound-specific mechanisms, especially for emerging DLCs such as polyhalogenated carbazoles (PHCZs), polychlorinated diphenyl sulfides (PCDPSs), and others, of which only a few investigations have been performed at present. Many of the toxic effects of emerging DLCs were observed to be predominantly mediated by the AHR because of their structural similarity as dioxins, and the in vitro TCDD-relative potencies of certain emerging DLC congeners are comparable to or even greater than the WHO-TEFs of OctaCDD, OctaCDF, and most coplanar PCBs. Due to the close relationship between AHR biology and environmental science, this review begins by providing novel insights into AHR signaling (canonical and non-canonical), AHR's biochemical properties (AHR structure, AHR-ligand interaction, AHR-DNA binding), and the variations during AHR transactivation. Then, AHR ligand classification and the corresponding mechanisms are discussed, especially the shared and compound-specific, AHR-mediated effects and mechanisms of emerging DLCs. Accordingly, a series of in vivo and in vitro toxicity evaluation methods based on the AHR signaling pathway are reviewed. In light of current advances, future research on traditional and emerging DLCs will enhance our understanding of their mechanisms, toxicity, potency, and ecological impacts.
Keywords: polychlorované bifenyly; dioxiny; Aryl hydrocarbon receptor; Dioxin-like compounds; receptory aromatických uhlovodíků; Toxicity evaluation; Dioxins; Molecular mechanisms; krysa rodu Rattus; zvířata; potkani Sprague-Dawley; Carbazoles; Receptors, Aryl Hydrocarbon; AHR ligands; Rats; Rats, Sprague-Dawley; Animals; karbazoly; Polychlorinated Biphenyls